Consumer participation in nurse education: A national survey of Australian universities. (4th March 2015) - Happell, Brenda; Platania‐Phung, Chris; Byrne, Louise; Wynaden, Dianne; Martin, Graham; Harris, Scott
Abstract Consumers of mental health services have an important role to play in the higher education of nursing students, by facilitating understanding of the experience of mental illness and instilling a culture of consumer participation. Yet the level of consumer participation in mental health nursing programmes in Australia is not known. The aim of the present study was to scope the level and nature of involvement of consumers in mental health nursing higher education in Australia. A cross‐sectional study was undertaken involving an internet survey of nurse academics who coordinate mental health nursing programmes in universities across Australia, representing 32 universities. Seventy‐eight percent of preregistration and 75% of post‐registration programmes report involving consumers. Programmes most commonly had one consumer (25%) and up to five. Face‐to‐face teaching, curriculum development, and membership‐to‐programme committees were the most regular types of involvement. The content was generally codeveloped by consumers and nurse academics (67.5%). The frequency of consumer involvement in the education of nursing students in Australia is surprisingly high. However, involvement is noticeably variable across types of activity (e.g. curriculum development, assessment), and tends to be minimal and ad hoc. Future research is required into the drivers of increased consumer involvement.